The Development and Pilot of a Technology-Based Intervention in the United States for Father’s Mental Health in the Perinatal Period - Jaime Hamil MPH (SAGE Publishing, 2021)
Paternal mental health is increasingly recognized as an important public health issue, with about 10% of men experiencing depression perinatally. Paternal depression is associated with less responsive parenting, greater parenting stress, and suboptimal child development. In response to a lack of existing interventions that directly focus on fathers’ mental health in the United States, we developed and pilot tested the Fathers and Babies (FAB) intervention for use with partners of women enrolled in home visiting (HV) programs. After a review of the extant literature, FAB was developed with input from HV stakeholders and infant mental health consultants. FAB was subsequently pilot tested with 30 father-mother dyads, with mixed-method data collected from a subset of intervention participants to assess intervention feasibility and acceptability and guide intervention refinement. Five themes related to FAB content and delivery considerations emerged from the initial focus groups that were used to guide FAB development. Mixed-method data collected during the pilot study established that fathers receiving FAB reported its content appropriate and thought it was feasible to receive the intervention. Several recommendations for FAB revisions were also provided. FAB is an innovative intervention developed for fathers from contemporary family structures that was well-received during its pilot testing. Feasibility and acceptability data suggest that fathers have favorable opinions about intervention content and delivery, while also highlighting areas for future revisions of FAB.